Empirical population and public health ethics: A review and critical analysis to advance robust empirical-normative inquiry. (May 2016) - Knight, Rod
The field of population and public health ethics (PPHE) has yet to fully embrace the generation of evidence as an important project. This article reviews the philosophical debates related to the 'empirical turn' in clinical bioethics, and critically analyses how PPHE has and can engage with the philosophical implications of generating empirical data within the task of normative inquiry. A set of five conceptual and theoretical issues pertaining to population health that are unresolved and could potentially benefit from empirical PPHE approaches to normative inquiry are discussed. Each issue differs from traditional empirical bioethical approaches, in that they emphasize (1) concerns related to the population, (2) 'upstream' policy-relevant health interventions – within and outside of the health care system and (3) the prevention of illness and disease. Within each theoretical issue, a conceptual example from population and public health approaches to HIV prevention and health promotion is interrogated. Based on the review and critical analysis, this article concludes that empirical-normative approaches to population and public health ethics would be most usefully pursued as an iterative project (rather than as a linear project), in which the normative informs the empirical questions to be asked and new empirical evidence constantly directs conceptualizations of what constitutes morally robust public health practices. Finally, a conceptualization of an empirical population and public health ethics is advanced in order to open up new interdisciplinary 'spaces', in which empirical and normative approaches to ethical inquiry are transparently (and ethically) integrated.